2012
DOI: 10.1002/ijc.27466
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of children affected by parental cancer and their use of specialized psychiatric services: The 1987 Finnish Birth Cohort study

Abstract: The studies reporting population-based estimates of the proportion of children with a parent suffering from cancer are very few. These children have been shown to suffer from psychological symptoms, but it is not known whether their use of psychiatric services is increased. Our study examined the prevalence of children affected by parental cancer at national level and whether these children use specialized psychiatric services more than their peers. The study is a retrospective population-based registry study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
(36 reference statements)
4
47
2
1
Order By: Relevance
“…The findings could also reflect the fact that parents with lung cancer had a higher risk of dying than parents with other types of cancers [53]. Furthermore, the temporal association with paternal and not maternal cancer could be due to the apparently increased mortality associated with paternal cancer, which has been suggested by other studies [53,54]. …”
Section: Discussionmentioning
confidence: 71%
“…The findings could also reflect the fact that parents with lung cancer had a higher risk of dying than parents with other types of cancers [53]. Furthermore, the temporal association with paternal and not maternal cancer could be due to the apparently increased mortality associated with paternal cancer, which has been suggested by other studies [53,54]. …”
Section: Discussionmentioning
confidence: 71%
“…Current international guidelines for oncological care explicitly recommend to involve the parental role of the patient and to involve minor children in supportive and psycho‐oncological care, if necessary . In Scandinavian countries, children of parents undergoing treatment should be considered routinely in healthcare clinical practice . Tailored support can help cancer patients during the course of the disease to reduce emotional distress and to enhance their QoL .…”
Section: Introductionmentioning
confidence: 99%
“…Multivariable logistic regression analysis revealed that family-centered support use can be predicted by the [3][4][5][6][7][8][9][10][11][12][13][14]. f According to the SF-8 Health Survey (range, 0-100).…”
Section: Prediction Of Seeking Psychosocial Support Servicesmentioning
confidence: 99%